Producing Sustainable Lightweight Geopolymer Concrete Using Waste Materials - Hilal Ameer A.; Nader Awaz S.; Kurji Badoor M. (Civil and Environmental Engineering)
A research has been undertaken to investigate the possibility of producing sustainable lightweight geopolymer material by using waste zeolite (zeolite molecular sieve) as aluminates and silicates source and at the same time as lightweight medium. This was done by totally or partially replacement of fly ash by waste zeolite particles. Six geopolymer mixes were designed and produced using different source materials (fly ash F, fly ash C and zeolite) and alkaline solution of sodium silicate and sodium hydroxide. From the results, it was found that using fly ash C resulted in producing geopolymer mix with higher density than those made with fly ash F (Gf mix). However, replacing the fly ash totally with the zeolite particles helped in producing lightweight geopolymer concrete (1600 kg/m3) by achieving about 27% weight reduction and gaining about 5.1 MPa compressive strength. Not only reducing CO2 emissions by adopting zeolite- based geopolymer binder (instead of cement paste) but also achieving operational energy saving by producing lightweight concrete was obtained from producing lightweight geopolymer concrete as constructional material.